Common and unique neural mechanisms of social and nonsocial conflict resolving and adaptation. (20th August 2022) - Wang, Jia-Xi; Li, Yuhe; Mu, Yan; Zhuang, Jin-Ying
Abstract: Humans often need to deal with various forms of information conflicts that arise when they receive inconsistent information. However, it remains unclear how we resolve them and whether the brain may recruit similar or distinct brain mechanisms to process different domains (e.g. social vs. nonsocial) of conflicts. To address this, we used functional magnetic resonance imaging and scanned 50 healthy participants when they were asked to perform 2 Stroop tasks with different forms of conflicts: social (i.e. face–gender incongruency) and nonsocial (i.e. color–word incongruency) conflicts. Neuroimaging results revealed that the ventral lateral prefrontal cortex was generally activated in processing incongruent versus congruent stimuli regardless of the task type, serving as a common mechanism for conflict resolving across domains. Notably, trial-based and model-based results jointly demonstrated that the dorsal and rostral medial prefrontal cortices were uniquely engaged in processing social incongruent stimuli, suggesting distinct neural substrates of social conflict resolving and adaptation. The findings uncover that the common but unique brain mechanisms are recruited when humans resolve and adapt to social conflicts.